Wychowanie w rodzinie chłopskiej w Drugiej Rzeczypospolitej - Samsel, Agata (Karkonoska Państwowa Szkoła Wyższa, 2011)
In 1918-1939 bringing up children in peasant families was severe and based on a system of punishments, usually corporal. It was a consequence of a common belief that only a hardened, tough and hardworking man is able to face hardpeasant reality which was leaving little place for weakness and fondness. Contrary to all appearances, such upbringing was to impose a system of values which placed the land, work, community and religion at the very top. Since the very young age the children used to be taught the value of land, the sense of responsibility and the awareness of being co-responsible for the family farm. It was implied that the public interest is superior to the individuals interest and the value of a person is estimated from the perspective of his/her work.
Keywords: rodzina chłopska; wychowanie; wartości; kultura; Druga Rzeczpospolita